LINE-1 Retroelements Complexed and Inhibited by Activation Induced Cytidine Deaminase - Metzner, Mirjam; Jäck, Hans-Martin; Wabl, Matthias (PLOS ONE, 2012)
LINE-1 (abbreviated L1) is a major class of retroelements in humans and mice. If unrestricted, retroelements accumulate in the cytoplasm and insert their DNA into the host genome, with the potential to cause autoimmune disease and cancer. Retroviruses and other retroelements are inhibited by proteins of the APOBEC family, of which activation-induced cytidine deaminase (AID) is a member. Although AID is mainly known for being a DNA mutator shaping the antibody repertoire in B lymphocytes, we found that AID also restricts de novo L1 integrations in B- and non-B-cell lines. It does so by decreasing the protein level of open reading frame 1 (ORF1) of both exogenous and endogenous L1. In activated B lymphocytes, AID deficiency increased L1 mRNA 1.6-fold and murine leukemia virus (MLV) mRNA 2.7-fold. In cell lines and activated B lymphocytes, AID forms cytoplasmic high-molecular-mass complexes with L1 mRNA, which may contribute to L1 restriction. Because AID-deficient activated B lymphocytes do not express ORF1 protein, we suggest that ORF1 protein expression is inhibited by additional restriction factors in these cells. The greater increase in MLV compared to L1 mRNA in AID-deficient activated B lymphocytes may indicate less strict surveillance of retrovirus.